Assessment of Landfill-emitted Gaseous Pollutants and Particulate Matters in Alimosho Local Government of Lagos state, Nigeria - Soile, Olutola Bob; Akiibinu, Moses O.; Bakare, Temitope E.; Olaoye, Gabriel O.; Oyeyiola, Felix A.; Adeola, Jacob A.; Alarape, Bolaji B.; Duduyemi, Olaniyi O.; Anetor, John I. (European Scientific Journal, ESJ, 2018)
Information on landfill-emitted pollutants in Nigeria cities has consequently become a priority. This study was designed to assess the air quality of landfill sites and the nearby communities in the Alimosho Local Government Area of Lagos state, Nigeria. Five public landfills in use since about thirty years ago were chosen for this study. A lightly populated area, free from other sources of air pollution served as control. Target points for the study were the centre of landfill (CLF), 50M from CLF, 100M from CLF, and a radius of 100M away from landfill. Levels of selected gaseous pollutants (NO2, O3, H2S and CO) and particulate matters (PM2.5 and PM10) were determined in the landfill environments and control (unpolluted area), using Aeroqual Series 500 with sensors for NO2, O3, H2S, CO, PM2.5 and PM10. The result showed that levels of H2S were significantly (p<0.001) higher at the CLF, 50M from CLF and 100M from CLF compared with unpolluted area. There was no significant (p>0.05) difference when the level of H2S in 100M radius was compared with the unpolluted area. Levels of CO were significantly (p<0.001) higher at the CLF, 50M from CLF, 100M from CLF and 100M radius compared with unpolluted area. The levels of O3 were significantly (p<0.001) higher at the CLF, 50M from CLF, 100M from CLF and 100M radius compared with unpolluted area. Levels of VOC were significantly (p<0.001) higher at the CLF, 50M from CLF, 100M from CLF and 100M radius compared with unpolluted area. The levels of NO2 were significantly (p<0.001) higher at the CLF, 50M from CLF, 100M from CLF and 100M radius compared with the unpolluted area. The levels of PM2.5 increased significantly (p<0.001) at the CLF, 50M from CLF, 100M from CLF and 100M radius compared with the unpolluted area. The levels of PM10 were also significantly (p< 0.001) higher at the CLF, 50M from CLF, 100M from CLF and 100M radius compared with the unpolluted area. In conclusion, communities close to landfills may be polluted with toxic gases and particulate matters. Further investigation is needed to validate the safe distance of residential areas from landfills to avert the risks of toxicity associated with gaseous pollutants.